The Moderating Effects of “Dark” Personality Traits and Message Vividness on the Persuasiveness of Terrorist Narrative Propaganda - Braddock, Kurt; Schumann, Sandy; Corner, Emily; Gill, Paul (Frontiers in Psychology, 2022)
Terrorism researchers have long discussed the role of psychology in the radicalization process. This work has included research on the respective roles of individual psychological traits and responses to terrorist propaganda. Unfortunately, much of this work has looked at psychological traits and responses to propaganda individually and has not considered how these factors may interact. This study redresses this gap in the literature. In this experiment (N = 268), participants were measured in terms of their narcissism, Machiavellianism, subclinical psychopath, and everyday sadism – collectively called the Dark Tetrad. Participants were then exposed to a vivid or nonvivid terrorist narrative (or a control message). Results indicate that Machiavellianism interacts with both narrative exposure and narrative vividness to amplify the persuasive effect of terrorist narratives. Neither narcissism, subclinical psychopathy, nor everyday sadism had such an effect. These results highlight the importance of considering the psychological traits of audiences when evaluating proclivity for radicalization via persuasion by terrorist narratives.